INTERACTIVE ACTIVITIES FOR EFFECTIVE LEARNING IN OVERCROWDED CLASSROOMS - Ayu, Mutiara (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
Involving students to participate in overcrowded classrooms activities is a challenging problem faced by teachers. They may spend much time to make students pay attention and concentrate on managing classroom activities. In Indonesia, many classrooms still go beyond thirty students, and it is common to be more than forty students in a class. As a result, the students are halfhearted and reluctant to participate actively in classroom activities. Promoting interactive activities such as forcing students’ engagement in group discussion and presentation seem to be alternative ways to aid students to learn English in a meaningful way and make them communicate effectively in English during teaching and learning process. Thus, the aim of this paper is to highlight some interactive activities for effective learning which can motivate and engage students with learning activities and create their interest in learning English in overcrowded classrooms.